Peningkatan Senyawa Fenolik Bekatul dengan SSF (Solid State Fermentation) sebagai Pencegah Kanker - Yeni Kurniati; Slamet Budijanto; Lilis Nuraida; Fitriya Nur Annisa Dewi (Puslitbang Tanaman Pangan, 2017)
Rice bran is a by-product of rice-milling process. The rice bran is a coarse powder substance that is rich in bioactive components, including ferulic acid, ?-oryzanol, ? -sitosterol, tokotrienol/tocopherol, trisin, r-coumaric, sinapic, syiringic and phytic acid. The phenolic compounds of rice bran have potential of preventing cancer. The compounds could be increased by SSF (Solid State Fermentation). Enzymes produced by microbes during the process of fermentation are amylase, xylanase, protease, lacase, esterase, and ? -glucosidase. Enzymes which help increase the phenolic compounds in the rice bran include: lacase, esterase and ? - glucosidase. Factors affecting the amount of increases of phenolic compounds in SSF are the types of microbes being used and duration of fermentation.